Der Campus als offene Bildungslandschaft: Perspektiven und Erwartungen an die Gestaltung von Quartieren als Bildungsraum. Issue 1 (2nd January 2022) - Klepp, Sarah; Million, Angela
Abstract: The development of educational infrastructure is increasingly linked to aspects of urban planning, urban design and architecture and discussed within the concept of educational landscapes, which links formal and non-formal educational settings and learning processes to spatial design. In practice, the Leitbild and design of educational campuses that are favoured by multi-professional stakeholders is one that also serves and is open to the neighbourhood. The aim of this research is to investigate the significance of the campus model and how the different interests and goals of the stakeholders in relation to the guiding idea of an initially openly conceived educational campus are negotiated in the process of planning and implementation. Empirical results from a case study are derived from an analysis of planning documents, site visits and interviews. The campus offers a robust model for educational policy and pedagogical as well as the planning and urban development goals of the stakeholders, and can also withstand ambivalent feelings and actions about aims and objectives within a campus development. The open educational campus can only be implemented in part because there is a lack of management strategies regarding how the openness can function and be maintained in everyday life on the campus. Instead, stakeholders see and accept the necessity of internal and external boundaries (especially fencing) without developing and negotiating far-reaching ideas about how these boundaries can be created productively as an educational space. English title: The campus as an open educational landscape. Perspectives and expectations for the design of neighbourhoods as educational spaces